Valine metabolite, 3-hydroxyisobutyrate, promotes lipid metabolism and cell proliferation in porcine mammary gland epithelial cells - Che, Long; Liu, Le; Xu, Mengmeng; Fan, Zongze; Niu, Lizhu; Chen, Yujie; Chang, Xueyuan; Zhou, Pan; Li, Mengyun; Deng, Hongyu; Chen, Wen (Frontiers in Nutrition, 2025)
Improving mammary gland epithelial cells proliferation through nutrition is an important approach for enhancing sow milk production and piglet growth. An intermediate metabolite of valine, 3-hydroxyisobutyrate (3-HIB), regulates cellular lipid metabolism. In the present study, we investigated the effects of 3-HIB on porcine mammary gland epithelial cells proliferation and lipid metabolism. The addition of an appropriate concentration of 3-HIB significantly increased mammary gland epithelial cell proliferation and the expression of proteins associated with cell proliferation. Compared to the control group, the addition of 0.4–0.8 mM 3-HIB increased the expression levels of mTOR signaling pathway-related proteins and the cell cycle protein, Cyclin D1, while inhibiting the expression of the cell cycle arrest protein, P27. The addition of 0.8 mM 3-HIB increased the triglyceride and lipid droplet content in the cells. The addition of 3-HIB increased the expression of proteins related to de novo fatty acid synthesis and transport, resulting in a marked increase in most polyunsaturated fatty acids in the 3-HIB-added group. Compared to the control group, the addition of 0.8 mM 3-HIB increased the expression levels of the fatty acid oxidation-related proteins, ACSL and CAD, ultimately increasing cellular ATP synthesis. In summary, the addition of 0.8 mM 3-HIB to porcine mammary gland epithelial cells promotes cell proliferation by enhancing lipid metabolism and the expression of cell proliferation-related proteins.